2016
DOI: 10.18632/oncotarget.14065
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical relevance of epithelial and mesenchymal markers in circulating tumor cells from colorectal cancer

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 44 publications
(62 reference statements)
6
76
0
Order By: Relevance
“…In the present study, we used the CanPatrol technique to count and characterize CTCs in a single test . The CanPatrol technique characterizes and classifies CTCs into epithelial, biophenotypic and mesenchymal phenotypes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we used the CanPatrol technique to count and characterize CTCs in a single test . The CanPatrol technique characterizes and classifies CTCs into epithelial, biophenotypic and mesenchymal phenotypes .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used the CanPatrol technique to count and characterize CTCs in a single test . The CanPatrol technique characterizes and classifies CTCs into epithelial, biophenotypic and mesenchymal phenotypes . Compared with the CellSearch platform, which uses anti‐EpCAM‐coated magnetic beads to capture CTCs, the CanPatrol technique uses an unbiased CTC isolation method that allows the isolation of CTCs that do not detectably express epithelial markers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTCs are released into the bloodstream during metastatic spread of the cancer through blood and are present as single cells or clusters [13]. They have been detected in various metastatic carcinomas including lung [14], breast [15,16], prostate [17], and colorectal cancer [18] but are extremely rare in healthy subjects and patients with nonmalignant diseases [19]. Even in patients with metastatic cancer, they occur on average at a frequency of 1 in 100 million cells and are mixed with approximately 10 million leukocytes and 5 billion erythrocytes per 1 ml blood [20].…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%
“…In endometrial cancer, CTCs were also found to express CD44 and ALDH (another cancer stemness marker), and in an orthotopic mouse model of colon cancer, CTCs were shown to have stem cell properties with significantly upregulated stem cell markers of DLG7 and BMI1 . It was also reported that CTCs and CSCs share a common feature in the process of epithelial‐mesenchymal transition (EMT), a prerequisite for CTC migration and CSC transformation . However, the detailed relationship and mechanism of how CTCs derive from CSCs and how CSCs promote CTC or CTC cluster formation and transport have yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%